Effects of lapatinib and trastuzumab on vascular endothelial growth factor in experimental corneal neovascularization - Kaya, Mehmet K.; Demir, Tamer; Bulut, Hakan; Akpolat, Nusret; Turgut, Burak (Wiley, 2015)
BackgroundThe aim of this study was to compare the effects of lapatinib and trastuzumab on vascular endothelial growth factor on experimental corneal neovascularization. MethodsA total of 35 Wistar albino rats were randomly divided into five groups, each containing seven animals. Corneas of rats in the control group were not cauterized and did not receive any treatment. A silver nitrate pencil was applied on the right corneas of rats in the non-control groups to induce corneal neovascularization. Rats in the sham, lapatinib, trastuzumab and lapatinib+trastuzumab groups were administered systemic saline, 50mg/kg lapatinib once a day orally by gavage, 4mg/kg trastuzumab once a day intraperitoneally, or 50mg/kg lapatinib once a day orally by gavage together with 4mg/kg trastuzumab once a day intraperitoneally, respectively, for 7 days. Rats were sacrificed on the eighth day, and corneas were excised using a 4-mm punch trephine. Vascular endothelial growth factor immunostaining in the corneal epithelial and stromal layers was evaluated. Staining intensities were determined semi-quantitatively, and corneal vascular endothelial growth factor levels were measured by enzyme-linked immunosorbent assay. ResultsThe mean immunostaining intensities of epithelial and stromal vascular endothelial growth factor in the control group were significantly lesser than those in the sham group (P<0.05). The mean immunostaining intensities of epithelial and stromal vascular endothelial growth factor and vascular endothelial growth factor enzyme-linked immunosorbent assay levels of corneas in all treatment groups (lapatinib, trastuzumab and lapatinib+trastuzumab groups) were lesser than those in the sham group (P<0.05); however, it was similar to those in the control group (P>0.05). ConclusionsIt is suggested that systemically administered lapatinib is more effective than systemically administered trastuzumab in preventing corneal neovascularization.
Keywords: corneal neovascularization; immunostaining; lapatinib; trastuzumab; VEGF